Surgical Treatment of Intra- and Juxtamedullary Spinal Cord Tumors: A Population Based Observational Cohort Study - Persson, Oscar; Fletcher-Sandersjöö, Alexander; Burström, Gustav; Edström, Erik; Elmi-Terander, Adrian (Frontiers in Neurology, 2019)
Objective: Intramedullary spinal cord tumors (IMSCT) are rare entities and high-level evidence regarding optimal treatment is lacking. We aim to describe the demographics, histopathological distribution, onset symptoms, treatment strategies and functional outcome for patients surgically treated for IMSCT. Methods: We performed a retrospective review of a consecutive population-based cohort of 95 patients who underwent surgery for intra- or juxtamedullary tumors at a single institution during the period 2004-2017. Results: When gross total resection (GTR) was achieved, we found no case of local tumor recurrence even in the absence of adjuvant radio- or chemotherapy. Meanwhile, we found a 50% progression rate on long-term MRI follow-up in patients where only a partial resection was possible. At long-term follow-up, there was no significant alteration in functional status, while a significant reduction in patient reported pain intensity, compared to preoperative status, was identified. Poor preoperative functional status and postoperative tumor remnant were identified as individual risk factors for further functional decline. Conclusion: Gross total resection, with minimal post-operative neurological deterioration, is possible in the majority of the cases, especially in the presence of an identifiable resection plane between tumor and healthy spinal cord. Since long-term progression-free survival could be achieved by GTR without additional adjuvant treatment, we emphasize that low-grade tumors should not be subject to radiotherapy. Treatment of high-grade or diffusely infiltrating tumors, tumor remnants, or metastases should be individualized.